Comparative study of strains of lactic acid bacteria contained in"Lactos" with imported probiotics - Shirchin, Demberel; Davaasuren, Ulzii-Uchral; Dugersuren, Javiyan; Khandsuren, Badgar; Lkhagvajav, Tsogtbaatar; Boldbaatar, Bulgan (Mongolian Journal of Agricultural Sciences, 2021)
We studied some biological properties of the local strains Lactobacillus helveticus LBMA44c and Lactobacillus delbruesckii subsp.bulgaricus LBMA65b contained in the domestic probiotic LACTOSA in compared to imported probiotics Lactobacillus, Linex-malysh and Acidophilus Probiotic Blend. The strains cultivated in liquid and solid selective MRS medium, obtained as a result of subsequent dilutions of a sample of the probiotics under study, perfectly demonstrated the general features of the morphological and cultural properties of lactic acid bacteria. The authors found that the indicators CFU/g of LACTOS (1.9-2.0x108 CFU/g) is not less than that of imported ones, in terms of the oxidation of nutrient media, it is the same as that of Acidophilus Probiotic Blend-and slightly lower than that of Linex and Lacto-Fit. Strains of lactic acid bacteria in all studied probiotics are well cultivated at 37, 45, 60 degrees (0C) and on a selective medium with an addition at the rate of 2, 4, 6 percent of natural bile and grows poorly on a medium with the addition of 4 and 6 percent NaCl. We also noted that the local strains in our LACTOS probiotic were relatively more resistant to antibiotics than imported ones, according to antibiotic resistance estimates. Thus, the local strains of lactic acid bacteria contained in the domestic probiotic under the LACTOS trademark do not differ from the imported ones. “Лактос” пробиотикт агуулагдах сүүн хүчлийн бактерийн шинж чанарыг импортынхтой харьцуулсан судалгаа “Лактос” пробиотикт агуулагдах сүүн хүчлийн бактерийн Lаctobacillus helveticus LBMA44c болон Lаctobacillus delbruesckii subsp.bulgaricus LВMА65b нутгийн омгийн эмнэлэг-биологийн чадавхын зарим үзүүлэлтийг импортын Lасто-Fit, Линекс Малыш №20, Acidophilus Probiotic Blend-ийнхтэй харьцуулан судлав. Судалгаанд хамрагдсан пробиотикуудын дээжний шингэлэлтээс MRS -ийн хатуу, шингэн сонгомол орчинд ургуулахад тэдгээр нь сүүн хүчлийн бактерийн өсгөвөржилт, хэлбэр зүйн нийтлэг шинж байдлыг үзүүлжээ. Пробиотикт агуулагдах амилах чадвартай бактерийн эсийн тоогоор Лактосынх (1,9-2,0х108КҮН/г) импортынхоос дутахгүй, харин орчныг хүчилсэг болгох идэвхээрээ Линекс Малыш, Lасtо-Fit-ээс бага зэрэг доогуур Acidophilus Probiotic Blend -тэй ойролцоо байна. Тэдгээр нь Цельсийн 37, 45, 60 хэмийн дулаанд болон 2, 4, 6 хувиар цөс нэмсэн тэжээлт орчинд сайн өсгөвөржих боловч цэвэр NaCl-ийн нэмэлт 4-6 хувь хүрэхэд пробиотикийн агууламж дахь сүүн хүчлийн бактерийн ургалтын эрчим дундаас доош гэсэн үнэлэмж рүү шилжсэн юм. Лактост агуулагдах сүү хүчлийн бактерийн омгууд нь судалгаанд ашигласан 5 төрлийн антибиотик тэсвэрлэх чадавхын дундаж үзүүлэлтээр импортын пробиотикийнхтой ойролцоо ажээ. Түлхүүр үг: пробиотик, сүүн хүчлийн бактери, тэсвэрт чанар, өсгөвөржилт This article author corrected: 31.12.2021